THE IMPLEMENTING OF THINK-PAIR-SHARE (TPS) STRATEGY IN TEACHING SPEAKING SKILLS - Nasir, Aco (JOURNAL OF ADVANCED ENGLISH STUDIES, 2018)
Currently, in teaching a language is claimed to be less effective when the Teaching activities are dominated by the instructor as known commonly teacher oriented. There are a lot of research report exposed that most of students are passive learners and only certain students respond learning activity. This is a marker that students are lazy to think as a form of familiarity is not active in the learning process and the habit of always relying on any material submitted by the teacher. This phenomenon is able to be overcome through one of cooperative learning strategy called Think Pair Share (TPS). This Model of TPS is a strategy whereas the students are demanded to be more active in individual thinking then discuss in pair and sharing in the whole class. This study is one of critical review toward previous research related to the Think-pair-Share strategy. In this case, this study aims to carry out the effect of the Think-Pair-Share implementation in teaching speaking skill. The findings indicate that there is a significant improvement in term of students’ ability in reading English after they are treated using Think-Pair-Share. However, this model requires a patient teacher to the students who has needed more attention.